2022
DOI: 10.3390/diagnostics12061422
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Tooth Prognosis Using Artificial Intelligence

Abstract: The accurate diagnosis of individual tooth prognosis has to be determined comprehensively in consideration of the broader treatment plan. The objective of this study was to establish an effective artificial intelligence (AI)-based module for an accurate tooth prognosis decision based on the Harvard School of Dental Medicine (HSDM) comprehensive treatment planning curriculum (CTPC). The tooth prognosis of 2359 teeth from 94 cases was evaluated with 1 to 5 levels (1—Hopeless, 5—Good condition for long term) by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…Lin et al suggested two models, first for identifying alveolar bone loss [ 22 ] and second for quantifying the extent of the bone loss [ 23 ]. Lee et al [ 24 ], based on the level of alveolar bone loss, developed a model formulated on a deep learning network of neurons to identify periodontally challenged molars and premolars and predict hopeless molars and premolars. Mol et al [ 25 ] and Carmody et al [ 26 ] presented models to categorize the severity of periapical lesions with regard to the diagnosis of periapical pathology.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Lin et al suggested two models, first for identifying alveolar bone loss [ 22 ] and second for quantifying the extent of the bone loss [ 23 ]. Lee et al [ 24 ], based on the level of alveolar bone loss, developed a model formulated on a deep learning network of neurons to identify periodontally challenged molars and premolars and predict hopeless molars and premolars. Mol et al [ 25 ] and Carmody et al [ 26 ] presented models to categorize the severity of periapical lesions with regard to the diagnosis of periapical pathology.…”
Section: Reviewmentioning
confidence: 99%
“…A useful tool for determining dental prognosis in light of the treatment strategy is an AI-based machine learning system. To determine a tooth's prognosis for long-term oral health and function, a thorough treatment strategy must be carefully reviewed [ 24 ].…”
Section: Reviewmentioning
confidence: 99%
“…Both the excluded studies made predictions without boosting the algorithm. Finally, five studies formed the basis of this study [ 17 , 18 , 19 , 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four of the five included studies were development/validation studies [ 17 , 18 , 19 , 20 ]. Another study was a development study [ 21 ]. The included studies were published between 2019 and 2022.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation